PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPS DENGAN MENGGUNAKAN MODEL TALKING STICK DI SEKOLAH DASAR - Juita, Erlinda; Suarman, Farida; Mansurdin, Mansurdin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research is done due to the fact that students’learning outcomes of Social Science subject were still low. This research aims at improving their learning outcomes by using Talking Stick Learning Model at Class V of SDN 08 Tanjung Medan, Pesisir Selatan. The subjects of the research were the teacher and 20 students of the school. The research result show that there has been some improvement. First, the planning phase was in the “good”criteria with the percentage of 8.00%. second, the implementation phase for the teacher’s and students’activities was categorized as ;excellent”criteria with the percentage of 13.75% Third, the students’leraning outcomes were in the “exccellent” criteria with the percentage of 50.00%. Thus,it can be concluded that the Talking Stick strategy has successfully improved the students’learning outcomes.Keywords: learning outcomes, ips, Talking Stick, elementary school.